SPECIFICITY OF SYMPTOMS OF PROFESSIONAL STRESS IN TEACHERS OF DIFFERENT TYPES OF SCHOOLS (Web of Teachers: Inderscience Research, 2024)
The article presents the results of a comparative analysis of the characteristics of the manifestation of professional stress and burnout syndrome among teachers of different types of schools: general education, correctional schools, lyceums. Varying degrees of susceptibility to burnout among teachers were identified.